Method for efficiently catalyzing and recovering gasoline product from oxygen-mediated waste polyolefin plastic

By using a physical mixing method of supporting metal catalyst and solid acid catalyst in the polyolefin aromatization reaction and optimizing the oxygen concentration, the problems of poor reaction activity and low aromatic selectivity are solved, and high-efficiency and low-cost polyolefin degradation and gasoline fuel are achieved.

CN119505946AActive Publication Date: 2025-02-25SUZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411683065.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

In the existing polyolefin aromatization reaction, the reaction activity is poor, the aromatic hydrocarbon selectivity is low, and the high temperature is required, resulting in high process cost and low efficiency.

Method used

The physical mixing method of supported metal catalyst and solid acid catalyst is used to test the catalytic performance under different oxygen concentrations, and the reaction conditions are optimized to improve catalytic activity and liquid gasoline selectivity.

Benefits of technology

High efficient selective degradation of polyolefins at lower reaction temperatures, achieving a plastic conversion of nearly 100 wt.% and a alkylbenzene selectivity of 77.5 mol.% and reducing process costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505946A_ABST
    Figure CN119505946A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of solid waste catalysis, and particularly relates to a method for efficiently catalyzing and recovering a gasoline product by using oxygen-mediated waste polyolefin plastics. The method comprises the following steps: mixing a metal-acid catalyst with waste polyolefin plastic, reacting in mixed gas containing oxygen under normal pressure, and separating reaction liquid to obtain a gasoline product, the metal-acid catalyst comprises a pretreated metal catalyst and a pretreated solid acid catalyst. According to the method, the optimal reaction conditions for preparing the aromatic chemicals by degrading the polyolefin are optimized under the condition of different oxygen concentrations by adopting the metal-acid catalyst, so that higher catalytic activity and selectivity of liquid gasoline products are obtained. In addition, the invention provides a novel air-assisted polyolefin catalytic recovery system for the first time, the limitation of harsh reaction conditions of traditional polyolefin catalytic recovery is solved, and large-scale application is expected to be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid waste catalysis, in particular to a method for efficiently catalyzing and recovering gasoline products from waste polyolefin plastics mediated by oxygen. Background Art

[0002] Plastics have been widely used since the 1950s due to their low cost, convenient use and excellent chemical stability. They can be found everywhere in daily life. With the continuous increase in plastic production, it is expected that 500Mt of waste plastics will be generated by 2050, and more than 80% of waste plastics will be landfilled or incinerated. Due to the good chemical stability of plastics, it is difficult to degrade in the natural environment, which not only pollutes the soil and water bodies, but also seriously invades the living space of organisms, causing serious environmental problems. Therefore, new recycling strategies and technologies are urgently needed to cope with the global plastic crisis. At present, chemical recycling technology of plastics is considered to be one of the effective strategies to solve the plastic crisis. Different from the low-value recycling of traditional mechanical recycling, this technology converts high-molecular-weight polymers into low-molecular-weight, high-value-added small molecules (such as solid paraffin, liquid fuel, gas products) by chemical means. This small molecule product obtained by recycling waste plastics can be reused as a raw material for chemical production reactions, realizing economic recycling and appreciation, and has attracted widespread attention from the industry.

[0003] Among many chemical recycling technologies, converting polyolefins into aromatic chemicals is considered to be a method with great industrial applications. Aromatic compounds are a class of chemicals with high economic value, among which benzene, toluene, and xylene are one of the main components of gasoline, and linear alkylbenzenes are key raw materials for the production of surfactants. These substances have become more attractive target products in plastic degradation due to their high economic value. Researchers use traditional pyrolysis reactions to make polyolefins undergo irregular CC bond cleavage at high temperatures to produce products such as alkanes, olefins, and aromatics. Finally, by cooling and condensation, aromatic hydrocarbons can be separated from the mixture, and finally aromatic chemicals that meet the requirements of chemical production can be obtained through refining. This process can effectively degrade and utilize waste plastics, and achieve efficient energy recycling by recovering the energy generated by high-temperature reactions. However, excessively high reaction temperatures and low aromatic selectivity have hindered the further development of this process. In order to reduce the severity of reaction conditions, reduce reaction time, improve the selectivity of aromatic hydrocarbons, and control product distribution, the introduction of appropriate catalysts for catalytic pyrolysis has gradually become the main process route for polyolefin degradation. Therefore, it is crucial to design a polyolefin preparation process with simple catalytic process, low cost, and high selectivity for aromatic chemicals.

[0004] The aromatization strategy of waste polyolefins is an emerging chemical recycling technology in recent years. Zeolite catalysts are generally used to degrade polyolefins into high-value-added liquid fuels. However, the aromatization reaction reported so far has too high a temperature requirement, and the product selectivity is often too low, making the economic benefits of this recycling strategy relatively low. Therefore, the selection of highly active and highly selective catalysts and advanced catalytic systems is crucial. The existing technologies are as follows:

[0005] (1) By using solid acid catalysts to degrade polyolefins into gasoline products. The optimal conditions for this technology are: under an argon atmosphere, a temperature of 500-700°C, and a reaction time of 24 hours, a 43.9 mol% aromatic selectivity can be obtained, and a series of low-value gases can be produced. (Reference source: J. Anal. Appl. Pyrolysis. 51, 107–126)

[0006] (2) By designing a fluidized bed device for pyrolysis and gasification, mixed plastics can be degraded into gasoline products. Polyolefins can be degraded into gasoline products without adding additional catalysts. The optimal reaction conditions are: argon atmosphere, 700 ° C, reaction time of 2 h, and 18.0 mol% aromatic selectivity can be obtained (Reference source: Energy & Fuels. 24, 1389–1395)

[0007] (3) By introducing greenhouse gas CO2, using Cu-Fe3O4 and Zn / ZSM-5 catalysts to convert polyolefins and CO2 into aromatic products and CO, achieving "double waste conversion". The optimal reaction conditions are: 3MPa CO2, 360℃, reaction time 1h, and 64wt.% aromatic selectivity can be obtained (Reference source: CCS Chem.1–23)

[0008] However, since the aromatization reaction of polyolefins is a typical endothermic reaction, the rate-determining step CH activation usually requires a higher temperature. Therefore, below 300°C, the activity is usually poor, the efficiency is low, and a longer reaction time is required to achieve a conversion rate of nearly 70wt.% and an aromatic selectivity of less than 50%. Therefore, it is urgent to develop a recovery method with high aromatic selectivity and high conversion rate under low temperature conditions. Summary of the invention

[0009] In order to solve the technical problem of low gasoline fuel yield in the current polyolefin aromatization reaction, the present invention provides a method for efficiently catalyzing and recovering gasoline products from waste polyolefin plastics mediated by oxygen. It is applied to the aromatization reaction of polyolefins to achieve efficient conversion of polyolefins into gasoline products. The present invention adopts a method of physically mixing a supported metal catalyst with a solid acid catalyst to test the catalytic performance under atmospheres with different oxygen concentrations to explore its optimal reaction conditions, thereby obtaining higher catalytic activity and liquid gasoline selectivity. In addition, the present invention also confirms that such catalysts can maintain high stability in an air catalytic environment, and achieve a plastic conversion rate of nearly 100wt.% and an alkylbenzene selectivity of 77.5mol%. The invention can not only achieve efficient and selective degradation of polyolefins at a relatively low reaction temperature, but also provide an important guiding idea for industrial polyolefin degradation to produce gasoline fuel.

[0010] The object of the present invention is to provide a method for efficiently catalyzing and recovering gasoline products from waste polyolefin plastics mediated by oxygen, comprising the following steps: mixing a metal-acid catalyst with waste polyolefin plastics, reacting in a mixed gas containing oxygen at normal pressure, separating the reaction liquid to obtain a gasoline product; the metal-acid catalyst comprises a pretreated metal catalyst and a pretreated solid acid catalyst. The gasoline product comprises gaseous low-carbon alkanes and liquid products, and the liquid products comprise alkylbenzenes, naphthalene, long-chain olefins and long-chain alkanes.

[0011] In some embodiments of the present invention, the oxygen content in the mixed gas is 10-50 Vol%;

[0012] The mixed gas further includes an inert gas, and the inert gas includes nitrogen and / or argon.

[0013] In the present invention, the mixed gas containing oxygen is preferably air.

[0014] In some embodiments of the present invention, the waste polyolefin plastic is selected from one or more of low-density polyethylene plastic, high-density polyethylene plastic, and polypropylene plastic;

[0015] The waste polyolefin plastic is in powder or block form, with a size of 1-5 cm.

[0016] In some embodiments of the present invention, the metal-acid catalyst is prepared by the following method:

[0017] drying the solid acid catalyst and the metal-based catalyst;

[0018] calcining the dried supported metal-based catalyst in a reducing gas atmosphere to obtain a pretreated metal catalyst;

[0019] calcining the dried solid acid catalyst in air at 500-600° C. for 2-4 hours to obtain a pretreated solid acid catalyst B;

[0020] The pretreated catalyst A and the pretreated catalyst B are mixed and ground to obtain the metal-acid catalyst.

[0021] In the present invention, the metal catalyst is reduced under a reducing atmosphere to ensure that the catalyst is in a metallic rather than reduced state before being put into the reaction.

[0022] In the present invention, the solid acid catalyst can be calcined to remove impurities on the surface, because zeolite is usually prepared by a cation exchange method, which requires the removal of impurities.

[0023] In some embodiments of the present invention, the solid acid catalyst is selected from one or more of HZSM-5, USY, and SAPO-34;

[0024] The metal in the metal-based catalyst is one or more of Pd, Pt, Ru, Ni, Ir, and Co;

[0025] The carrier of the metal-based catalyst is one or more of C, CeO2, SiO2, and TiO2;

[0026] Specifically, the metal-based catalyst of the present invention includes one or more of Ru / C, Ni / C, Pd / C, Ir / C, Ru / CeO2, Ru / SiO2, and Ru / TiO2 catalysts, preferably Ru / C, Ni / C, Pd / C, and Ir / C; further preferred is Ru / C; all of the above catalysts are products available on the market.

[0027] The metal loading in the metal-based catalyst is 1-10 wt.%.

[0028] In some embodiments of the present invention, the reducing gas atmosphere includes hydrogen and an inactive gas, wherein the concentration of hydrogen is 5-10 Vol%, and the inactive gas is nitrogen and / or argon.

[0029] In some embodiments of the present invention, the calcination temperature is 300° C. and the calcination time is 2-4 hours.

[0030] In some embodiments of the present invention, the mass ratio of the pretreated catalyst A to the pretreated catalyst B is 1:(4-8).

[0031] In some embodiments of the present invention, the mass ratio of the pretreated metal catalyst, the pretreated solid acid catalyst and the waste polyolefin plastic is 1:(4-8):(20-100).

[0032] In some embodiments of the present invention, the reaction conditions are as follows: the reaction temperature is 220-300° C., the reaction time is 1-12 h, and the reaction stirring rate is 200-1200 rpm.

[0033] The above technical solution of the present invention has the following advantages compared with the prior art:

[0034] (1) The present invention uses O2 for the first time to promote the aromatization reaction of polyolefins, solving the problems of poor reactivity and low selectivity of aromatics in the preparation of aromatics by traditional plastic degradation. The present invention improves the problem of slow CH bond activation in the aromatization reaction of polyolefins by introducing oxygen, because the introduction of O2 can play a role in thermodynamic series connection, breaking the previous thermodynamically limited barrier. On the other hand, oxygen consumes the H2 produced by the aromatization reaction in time, which kinetically helps the overall reaction equilibrium to move forward.

[0035] (2) The present invention can utilize the "quasi-combustion reaction" of O2 on the catalyst surface to thermodynamically control the overall aromatization reaction, thereby significantly reducing the temperature of the polyolefin aromatization reaction and thus reducing the process cost.

[0036] (3) The catalyst of the present invention has extremely high stability under air conditions and still maintains high catalytic activity and selectivity for liquid gasoline after 5 reaction cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0038] Figure 1 This is a physical picture of a 50ml reactor of the present invention;

[0039] Figure 2 The performance diagram of the polyolefin aromatization at different temperatures under normal pressure air of the present invention;

[0040] Figure 3 The liquid selectivity of the polyolefin aromatization reaction under the mixed gas with different O2 contents of the present invention;

[0041] Figure 4 The liquid selectivity of the polyolefin aromatization reaction under the mixed gas with different O2 contents of the present invention;

[0042] Figure 5 The performance diagram of the polyolefin aromatization at different temperatures under normal pressure air of the present invention;

[0043] Figure 6 This is a performance diagram of the polyolefin aromatization stability test under normal pressure air of the present invention;

[0044] Figure 7 This is a physical picture of the 2L reactor of the present invention;

[0045] Figure 8 This is a physical picture of the liquid gasoline product after the large-scale polyolefin aromatization reaction of the present invention;

[0046] Fig. 9 It is a performance diagram of the liquid yield after the atmospheric pressure aromatization reaction of the polyolefin of the present invention. DETAILED DESCRIPTION

[0047] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0048] Example 1

[0049] This embodiment provides a method for efficiently catalyzing and recovering gasoline products from waste polyolefin plastics mediated by oxygen, as shown below:

[0050] 1. Preparation of catalyst materials, as follows:

[0051] (1) Weigh 50 g of commercial HZSM-5 and 25 g of commercial Ru / C, Ni / C, Pd / C, Ir / C, Ru / CeO2, Ru / SiO2, and Ru / TiO2 catalysts respectively and place them in an oven at 100 °C for 8 h to ensure that there is no moisture in them.

[0052] (2) Reduction treatment: The commercial Ru / C, Ni / C, Pd / C, and Ir / C catalysts obtained by drying in step (1) are placed in a tubular furnace, respectively, and calcined at 300°C for 2 h in a H2 / Ar (H2 / 5 Vol%) mixed gas to obtain reduced metal catalysts.

[0053] (3) Calcination treatment: The dried HZSM-5 catalyst obtained in step (1) is placed in a muffle furnace and calcined in air at 500° C. for 2 h to obtain a calcined HZSM-5 catalyst.

[0054] (4) Grinding: The reduced metal catalyst and the calcined HZSM-5 catalyst are physically mixed in a mass ratio of 1:4, and the mixed catalyst powders of metals Ru, Ni, Pd, and Ir are obtained after repeated grinding.

[0055] (II) Application of catalyst materials

[0056] (1) Weigh 250 mg of the mixed catalyst powder containing metals Ru, Ni, Pd and Ir prepared in step (i), of which 50 mg is the reduced metal catalyst and 200 mg is the calcined HZSM-5 zeolite.

[0057] (2) Weigh 1g of low-density polyolefin powder (LDPE) and put it into a high-pressure reactor. See the schematic diagram of the 50ml reactor. Figure 1 . Under air atmosphere, the reaction temperature is 280°C, the stirring rate is 400rpm, and the reaction time is 12h. After the reaction is completed, an air bag is used to collect the remaining gas after the reaction; then dichloromethane is used to dissolve and disperse the liquid product and the solid product, and the liquid product and the solid product are separated by centrifugation, and the liquid product dissolved in dichloromethane is collected, and the solid product is washed and collected, and then placed in an oven at 80°C for drying. The gaseous products generated by the reaction are detected online by gas chromatograph. The liquid products are detected by gel permeation chromatography, nuclear magnetic resonance, and gas chromatograph. See the catalytic result diagram. Figure 2 , it can be seen from the figure that the mixed catalyst powder containing metal Ru / C exhibits the best catalytic performance.

[0058] Example 2

[0059] 1. Preparation of catalyst materials, as follows:

[0060] The preparation of the catalyst material is similar to that of Example 1, except that Ru / C in Example 1 is replaced by Ru / CeO2, Ru / SiO2, and Ru / TiO2 metal-supported catalysts, and other conditions are the same as those of Example 1. Finally, reduced Ru / CeO2, Ru / SiO2, and Ru / TiO2 metal mixed catalyst powders are prepared.

[0061] (II) Application of catalyst materials

[0062] (1) Take 250 mg of the reduced Ru / C metal mixed catalyst powder obtained in Example 1 and the Ru / CeO2, Ru / SiO2, and Ru / TiO2 metal mixed catalyst powders obtained in this example, respectively, of which the reduced mixed catalyst powder corresponding to each metal accounts for 50 mg and the calcined HZSM-5 zeolite accounts for 200 mg.

[0063] (2) Weigh 1g of low-density polyolefin powder (LDPE) and put it into a high-pressure reactor. See the schematic diagram of the 50ml reactor. Figure 1. Under air atmosphere, the reaction temperature is 280°C, the stirring rate is 400rpm, and the reaction time is 12h. After the reaction is completed, an air bag is used to collect the remaining gas after the reaction; then dichloromethane is used to dissolve and disperse the liquid product and the solid product, and the liquid product and the solid product are separated by centrifugation, and the liquid product dissolved in dichloromethane is collected, and the solid product is washed and collected, and then placed in an oven at 80°C for drying. The gaseous products generated by the reaction are detected online by gas chromatograph. The liquid products are detected by gel permeation chromatography, nuclear magnetic resonance, and gas chromatograph. See the catalytic result diagram. Figure 3 As can be seen from the figure, metal Ru loaded on a carbon-based carrier exhibits the best catalytic performance, which may be attributed to the fact that the carbon-based carrier is a hydrophobic carrier, and the plastic in the molten state is also hydrophobic, which is more conducive to mass transfer.

[0064] Example 3

[0065] Weigh 250 mg of the mixed catalyst powder containing metal Ru prepared in Example 1, of which 50 mg is reduced Ru / C catalyst, 5 wt.% of Ru loading, and 200 mg of calcined HZSM-5 zeolite. Weigh 1 g of low-density polyolefin powder (LDPE) and put it into a high-pressure reactor. See the schematic diagram of the 50 ml reactor for details. Figure 1 . Regulate the mixed gas of O2 and Ar in different proportions (the O2 contents are 5Vol%, 10Vol%, 20Vol%, and 50Vol%, respectively), the reaction temperature is 280°C, the stirring rate is 400rpm, and the reaction time is 12h. After the reaction is completed, use an air bag to collect the remaining gas after the reaction; then use dichloromethane to dissolve and disperse the liquid product and the solid product, separate the liquid product and the solid product by centrifugation, collect the liquid product dissolved in dichloromethane, wash and collect the solid product, and put it in an oven at 80°C for drying. The gaseous products generated by the reaction are detected online by gas chromatograph. The liquid products are detected by gel permeation chromatograph, nuclear magnetic resonance spectroscopy, and gas chromatograph. See the catalytic result figure. Figure 4 As can be seen from the figure, the best catalytic performance is shown when the O2 volume content is 20%.

[0066] Example 4

[0067] Weigh 250 mg of the mixed catalyst powder prepared in Example 1, of which Ru / C accounts for 50 mg, the loading amount of Ru is 5wt.%, and HZSM-5 zeolite accounts for 200 mg. Weigh 1 g of low-density polyolefin powder (LDPE) and put it into a 50 ml reactor. Use air to purge at least 5 times, and react after the pressure of the reactor is maintained at normal pressure. The reaction temperatures are set to 220°C, 250°C, and 280°C, respectively, the stirring rate is 400 rpm, and the reaction time is 12 h. After the reaction is completed, use an air bag to collect the remaining gas after the reaction; then use dichloromethane to dissolve and disperse the liquid product and the solid product, separate the liquid product and the solid product by centrifugation, collect the liquid product dissolved in dichloromethane, wash and collect the solid product, and put it in an oven at 80°C for drying. The gas products generated by the reaction are detected online by gas chromatograph. The liquid product is detected by gel permeation chromatograph, nuclear magnetic resonance spectroscopy, and gas chromatograph. See the catalytic result diagram Figure 5 As can be seen from the figure, the oxygen-mediated polyolefin aromatization reaction system is most affected by time. At 250°C, a plastic conversion rate of more than 80wt% can be achieved in 12h.

[0068] Example 5

[0069] This example provides a recycling and regeneration experiment of the mixed catalyst powder, which is specifically as follows:

[0070] (1) Collect the mixed catalyst obtained after application in Example 1.

[0071] (2) Wash with hot toluene at 180°C for 5 times, collect the mixed catalyst after reaction by centrifugation and dry it in an oven at 80°C, then calcine it with 5 Vol.% H2 / Ar mixed gas at 300°C in a tubular furnace for 2h for catalyst regeneration.

[0072] (3) After the reaction, the catalyst usually has a loss of 10wt.%, and 25mg of mixed catalyst is added, of which 5mg is reduced metal catalyst Ru / C and 20mg is calcined HZSM-5 zeolite, for subsequent cyclic stability test. The catalyst and plastic are placed at the bottom of the reactor, washed with air at least 5 times, and maintained at normal pressure. The reaction temperature is 250°C, the stirring rate is 400rpm, and the reaction time is 12h. After the reaction is completed, an air bag is used to collect the remaining gas after the reaction; then, dichloromethane is used to dissolve and disperse the liquid product and the solid product, and the liquid product and the solid product are separated by centrifugation, and the liquid product dissolved in dichloromethane is collected, and the solid product is washed and collected, and placed in an oven at 80°C for drying. The gas product generated by the reaction is detected online by gas chromatograph. The liquid product is detected by gel permeation chromatography, nuclear magnetic resonance, and gas chromatograph. The stability test results are shown in Figure 6As can be seen from the figure, the catalyst has extremely strong stability, and the liquid selectivity is still maintained above 60 mol% after multiple cycles.

[0073] Example 6

[0074] Weigh 25g of the physical mixed catalyst prepared in Example 1, of which 5g is the reduced metal catalyst Ru / C, and the loading amount of Ru is 5wt.%, and 20g is the calcined HZSM-5 zeolite. Weigh 100g of low-density polyolefin powder (LDPE) and put it into a 2L reactor (see the schematic diagram of the 2L reactor). Figure 7 ). Put the catalyst and plastic into the bottom of the reactor, purge with air at least 5 times, and maintain normal pressure. The reaction temperature is 250°C, the stirring rate is 400rpm, and the reaction time is 12h. After the reaction is completed, use an air bag to collect the remaining gas after the reaction; then use dichloromethane to dissolve and disperse the liquid product and the solid product, separate the liquid product and the solid product by centrifugation, and collect the liquid product dissolved in dichloromethane (see product diagram Figure 8 ), the solid product was washed and collected, and then placed in an oven at 80°C for drying. The gaseous product generated by the reaction was detected online by a gas chromatograph. The liquid product was detected by a gel permeation chromatograph, a nuclear magnetic resonance spectrometer, and a gas chromatograph.

[0075] Example 7

[0076] Weigh 2.5g of the physical mixed catalyst prepared in Example 1, of which the reduced metal catalyst Ru / C accounts for 0.5g, the Ru loading is 5wt.%, and the calcined HZSM-5 zeolite accounts for 2g. Weigh 10g of low-density polyolefin powder (LDPE) and put it into a 50ml three-necked flask. Put the catalyst and plastic at the bottom of the three-necked flask. The reaction temperature is 250°C, the stirring rate is 200rpm, and the reaction time is 4h. After the reaction is completed, use dichloromethane to dissolve and disperse the liquid product and the solid product, separate the liquid product and the solid product by centrifugation, collect the liquid product dissolved in dichloromethane, wash and collect the solid product, and put it in an oven at 80°C for drying. The gaseous product generated by the reaction is detected online by gas chromatograph. The liquid product is detected by gel permeation chromatograph, nuclear magnetic resonance spectroscopy, and gas chromatograph. The catalytic test results are shown in Fig. 9 , it can be seen from the figure that the reaction can still run in an open system at normal pressure and remains stable after multiple cycles.

[0077] in conclusion

[0078] The following results were obtained through analysis and calculation: Under the conditions of 280°C, 20% O2 (air) mixed gas ratio, reaction time of 12h and stirring rate of 400rpm, the reduced metal catalyst Ru / C and HZSM-5 mixed catalyst showed the best activity and the highest gasoline product selectivity, and showed good prospects for industrial application in large-scale experiments.

[0079] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A method for efficiently catalyzing and recovering gasoline products from waste polyolefin plastics mediated by oxygen, characterized in that: The following steps are involved: The metal-acid catalyst is mixed with waste polyolefin plastics, and reacted in a mixed gas containing oxygen under normal pressure, and the reaction liquid is separated to obtain a gasoline product; the metal-acid catalyst includes a pretreated metal catalyst and a pretreated solid acid catalyst.

2. The method for efficiently catalyzing and recovering gasoline products from waste polyolefin plastics mediated by oxygen according to claim 1, characterized in that: The oxygen content in the mixed gas is 10-50 Vol%; The mixed gas further includes an inert gas, and the inert gas includes nitrogen and / or argon.

3. The method for efficiently catalyzing and recovering gasoline products from waste polyolefin plastics mediated by oxygen according to claim 1, characterized in that: The waste polyolefin plastic is selected from one or more of low-density polyethylene plastic, high-density polyethylene plastic, and polypropylene plastic; The waste polyolefin plastic is in powder or block form, with a size of 1-5 cm.

4. The method for efficiently catalyzing and recovering gasoline products from waste polyolefin plastics mediated by oxygen according to claim 1, characterized in that: The metal-acid catalyst is prepared by the following method: drying the solid acid catalyst and the metal-based catalyst; calcining the dried metal-based catalyst in a reducing gas atmosphere to obtain a pretreated metal catalyst; calcining the dried solid acid catalyst in air at 500-600° C. for 2-4 hours to obtain a pretreated solid acid catalyst B; The pretreated catalyst A and the pretreated catalyst B are mixed and ground to obtain the metal-acid catalyst.

5. The method for efficiently catalyzing and recovering gasoline products from waste polyolefin plastics mediated by oxygen according to claim 4, characterized in that: The solid acid catalyst is selected from one or more of HZSM-5, USY, and SAPO-34; The metal in the metal-based catalyst is one or more of Pd, Pt, Ru, Ni, Ir, and Co; The carrier of the metal-based catalyst is one or more of C, CeO2, SiO2, and TiO2; The metal loading in the metal-based catalyst is 1-10 wt.%.

6. The method for efficiently catalyzing and recovering gasoline products from waste polyolefin plastics mediated by oxygen according to claim 4, characterized in that: The reducing gas atmosphere includes hydrogen and an inactive gas, wherein the concentration of hydrogen is 5-10 Vol%, and the inactive gas is nitrogen and / or argon.

7. The method for efficiently catalyzing and recovering gasoline products from waste polyolefin plastics mediated by oxygen according to claim 4, characterized in that: The calcination temperature is 300°C and the calcination time is 2-4h.

8. The method for efficiently catalyzing and recovering gasoline products from waste polyolefin plastics mediated by oxygen according to claim 4, characterized in that: The mass ratio of the pretreated catalyst A to the pretreated catalyst B is 1:(4-8).

9. The method for efficiently catalyzing the recovery of gasoline products from waste polyolefin plastics mediated by oxygen according to claim 1, characterized in that: The mass ratio of the pretreated metal catalyst, the pretreated solid acid catalyst and the waste polyolefin plastic is 1:(4-8):(20-100).

10. The method for efficiently catalyzing and recovering gasoline products from waste polyolefin plastics mediated by oxygen according to claim 1, characterized in that: The reaction conditions are as follows: the reaction temperature is 220-300° C., the reaction time is 1-12 h, and the reaction stirring rate is 200-1200 rpm.

Citation Information

Patent Citations

  • Method for directionally preparing aromatic hydrocarbon, synthesis gas, olefin and carbon material by coupling waste plastic pyrolysis with carbon dioxide reduction

    CN115161051A

  • Catalyst and method for preparing high-quality gasoline by coupling conversion of CO2 and polyolefin

    CN117299191A

  • Method for low-temperature aromatization of waste polyolefin or aliphatic hydrocarbon

    CN118240584A

  • Oxidative cracking of hydrocarbons

    US11046892B1

  • Efficient and selective conversion of high-density polyethylene into valuable hydrocarbons

    US20230211326A1